TI_GERICHTE 52.2019.366 vom 12. Juni 2019 , Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida - TI Tribunale d'appello (2019)
Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida